O uso dos recursos linguísticos de modalidade epistêmica e evidencialidade na construção discursiva das redações de nota máxima do ENEM - Bernardo, Kellivania da Silva (2023)
This research, conducted in the area of Linguistic Description and Analysis, is based on Functional Discourse Grammar (FDG) and aims to analyze and describe the manifestation of epistemic modality and evidentiality in ENEM essays. The corpus is composed of 45 essays that scored 1.000 produced in the regular editions of the ENEM test from 2013 to 2019. In order to fulfill the determined objective, the research is analyzed the following parameters: 1) Domains - Epistemic Modality and Evidentiality; 2) Epistemic Modality: Objective and Subjective; 3) Evidentiality - subcategories (types of access and types of sources); 4) Meanings and Effects; 5) Linguistic resources of modal/evidential expression; 6) Textual scheme; 7) Adequacy and Functionality of modal/evidential resources. The results obtained through the use of the SPSS (Statistical Package for Social Science) computer system reveal that the manifestations of Epistemic Modality and Evidentiality fulfill their functions in the argumentative construction on the analyzed productions. In the case of the epistemic modality, these manifestations express the author's commitment to the truth he says, to what he believes to be real or possible. To this end, the author constructs his discourse with more frequent use of epistemic modals and the subjective orientation with the target in the Propositional Content. In occurrences of modalization, the sense of certainty is the most expressed. In the case of Evidentiality, which concerns the exposition of the source of information, the results show that the most recurrent evidential resources were the embedding verbs, in the use of Reportativity with 3rd person defined source, meeting the purpose of giving more credibility to the information presented in the Communicated Content. The modal and evidential resources were mostly found in the development of the essays, and are indeed qualified as functional and appropriate to the context.